Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - P.4 - Factoring Polynomials - Exercises - Page 40: 84



Work Step by Step

Using factoring, we find: $kQx-kx^2=(k)Qx-(k)x^2=k(Qx-x^2)=k[Q(x)-x(x)]=kx(Q-x)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.